Strategi Talent Management Berbasis Digital dalam Meningkatkan Retensi dan Loyalitas Karyawan Generasi Milenial dan Gen Z - Riko Mersandro Permana; Hizbul Khootimah Azzaakiyyah; Ahmad Junaidi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the role of digital talent management strategies in improving employee retention and loyalty among Millennials and Generation Z employees. The research method employed a qualitative approach with a literature review design and descriptive analysis. Data were obtained from 41 selected scientific articles sourced from Google Scholar with publication years ranging from 1964–2026, which were selected from an initial 50 articles based on relevance and scientific quality. The data analysis techniques included theme categorization, interpretation, and synthesis. The findings indicate that the implementation of digital talent management through data-based HR systems, digital learning platforms, and employee engagement systems can enhance employees’ attachment to the organization. Case studies from global and national companies such as Google and Tokopedia strengthen the finding that digitalization contributes to increasing employee retention and loyalty, especially among younger generations. The success of implementation is strongly influenced by organizational readiness in integrating technology with a human-centered approach. This study is limited by its reliance on literature review without direct primary data and its greater focus on large companies and the technology sector, so the generalization of findings should be interpreted cautiously. Future research is recommended to apply mixed methods approaches, expand studies to SMEs and non-technology organizations, and develop more integrated AI-based digital talent management systems.